Mu ̈ntz’s Theorem in 2-Inner Product Spaces and It’s Applications in Economics - Kumar, Nand Kishor; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2024)
This study establishes a 2-inner product space, as well as its basic attributes and proof. The proof of Müntz’s theorem in 2-inner product spaces was demonstrated. Müntz’s Theorem finds a natural extension and application in the realm of 2-inner product spaces. By understanding the conditions under which certain functions form dense subsets, we can gain insights into the approximation properties and structural characteristics of these spaces. Further research may explore specific examples and ramifications of Müntz’s theorem in diverse areas of mathematics and their applications. Müntz’s Theorem provides valuable insights in economics by addressing the question of how well economic functions can be approximated when the available data or model inputs are restricted.